1999
DOI: 10.1046/j.1365-313x.1999.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana AtHAL3: a flavoprotein related to salt and osmotic tolerance and plant growth

Abstract: SummaryWe have isolated two Arabidopsis thaliana genes, AtHAL3a and AtHAL3b, showing homology with HAL3, a yeast protein which regulates the cell cycle and tolerance to salt stress through inhibition of the PPZ1 type-1 protein phosphatase. Expression of AtHAL3a in yeast hal3 mutants partially complements their LiCl sensitivity, suggesting possible conserved functions between both proteins. AtHAL3a and AtHAL3b are induced by salt stress and AtHAL3a is the most expressed in non-stressed plants, particularly in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(82 citation statements)
references
References 39 publications
8
74
0
Order By: Relevance
“…Arabidopsis mutants in the PDX1.3 gene for pyridoxal 59-phosphate synthase were found to be hypersensitive to salt, osmotic, and oxidative stress (Chen and Xiong, 2005;Titiz et al, 2006). (2) Pantothenate/coenzyme A: The Arabidopsis HAL3A (HALOTOLERANCE DETERMINANT 3A) gene, first identified for its relation to stress tolerance (EspinosaRuiz et al, 1999), was shown to code for a key enzyme in pantothenate conversion to coenzyme A (Kupke et al, 2001), and HAL3A overexpression increased salt tolerance (Espinosa-Ruiz et al, 1999;Yonamine et al, 2004). (3) .…”
Section: Modern Evidencementioning
confidence: 99%
“…Arabidopsis mutants in the PDX1.3 gene for pyridoxal 59-phosphate synthase were found to be hypersensitive to salt, osmotic, and oxidative stress (Chen and Xiong, 2005;Titiz et al, 2006). (2) Pantothenate/coenzyme A: The Arabidopsis HAL3A (HALOTOLERANCE DETERMINANT 3A) gene, first identified for its relation to stress tolerance (EspinosaRuiz et al, 1999), was shown to code for a key enzyme in pantothenate conversion to coenzyme A (Kupke et al, 2001), and HAL3A overexpression increased salt tolerance (Espinosa-Ruiz et al, 1999;Yonamine et al, 2004). (3) .…”
Section: Modern Evidencementioning
confidence: 99%
“…Plants that overexpress the gene encoding the AtHAL3A PPCDC showed improved growth under salt and osmotic stress (Espinosa-Ruiz et al, 1999). Overexpression of tobacco (Nicotiana tabacum) HAL3 also enhanced salt and osmotic stress tolerance in cultured tobacco cells (Yonamine et al, 2004).…”
Section: Overexpression Of Ppat Leads To Enhanced Growth and Salt/osmmentioning
confidence: 99%
“…For instance, in oilseed plants the use of storage lipids during early seedling establishment is a key process for plant survival that is CoA dependent (Graham and Eastmond, 2002). Additionally, as CoA biosynthesis appears to be a sensitive step in plants under salt stress (Espinosa-Ruiz et al, 1999;Yonamine et al, 2004), an improved knowledge of this pathway might help our understanding of how plants cope with abiotic stresses. Finally, as the CoA biosynthetic pathway is evolutionarily conserved, its study in plants might have clinical relevance, as defects in this pathway lead to a human neurodegenerative disease (Zhou et al, 2001).…”
mentioning
confidence: 99%
“…HAL3A is a flavoprotein that catalyzes the decarboxylation of PPC to 4#-phosphopantetheine (Kupke et al, 2001;HernandezAcosta et al, 2002), and overexpression of this enzyme leads to improved plant tolerance to salt and osmotic stress (Espinosa-Ruiz et al, 1999;Yonamine et al, 2004). Two highly homologous genes, HAL3A (At3g18030) and HAL3B (At1g48605), are present in the Arabidopsis genome.…”
mentioning
confidence: 99%